A WOMAN WITH SPORADIC HEMOPHILIA-B DIE BECAUSE OF CEREBRAL BLEEDING: A Rare Case in Bali-Indonesia - Suega, Ketut (BALI MEDICAL JOURNAL, 2015)
Background: Hemophilias are groups of blood clotting disorder caused by deficiency of blood clotting factors which is X-linked recessively inherited and explain why mostly man is the affected victim. But on an extremely rare condition a women can have hemophilia due to several reasons and sporadic hemophilia is used to describe when hemophilia appeared without ascent and decent history of hemophilia. A 38 years old women with a peripheral spontaneous bleeding for two days although an open flap and a cauterization to stop the bleeding has been applied. She was the third child of 7 children in the family, 3 of them were man with normal life and 4 women also have no history of bleeding. Her parent and grand-parent were all dead because of aging problems. She also has 2 sons with ages of 10 and 13 years, respectively, live normally. Results: factor VIII activity 192 seconds (control: 80 seconds), factor IX activity 2 seconds (control: 111 seconds), hence patient was considered suffered from sporadic haemophilia-B due to low level of factor IX 1.8% and bleeding episodes mimicking clinical presentation of classical hemophilia patients while no known history of having hemophiliac family. The different diagnose were Von Willebrand Diisease (VWD), symptomatic carriers, acquired hemophilia. After several admissions and repeatedly bleeding episodes patient died because of intra cerebral bleeding.
Keywords: hemophilia-B; sporadic hemophilia; cerebral; bleeding.